2009
DOI: 10.1002/ibd.20693
|View full text |Cite
|
Sign up to set email alerts
|

Profile of depression in adolescents with inflammatory bowel disease: Implications for treatment

Abstract: Background-The purpose was to determine the utility of including neurovegetative symptoms in assessments of depression in youth with inflammatory bowel disease (IBD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…Th e interactions between psychologic stress and the immune and digestive systems are likely to be complex and deeply intertwined ( 7,44 ).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Th e interactions between psychologic stress and the immune and digestive systems are likely to be complex and deeply intertwined ( 7,44 ).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Therapeutic strategies to induce remission are critical to maximise growth potential and velocity and ensure that developmental milestones are obtained within normal timescales,15 while addressing concerns over body image 16. Corticosteroid use can result in stunted growth and puberty in AYP and is associated with reduced quality of life and an increased psychological distress and depression 17 18. Healthcare providers in adult and paediatric settings must monitor growth, pubertal development and related psychological morbidity.…”
Section: Monitoring Clinical Disease In Ayp With Ibdmentioning
confidence: 99%
“…Sleep disturbances have been associated with the exacerbation of chronic inflammation, especially related to pain and fatigue, and a decreased health-related quality of life. In a pediatric population of 283 patients with IBD, Szigethy et al reported difficulty sleeping in 60% of patients, and 45% of patients reported fatigue on a clinical disease index [49] . Animal models have shown that the cytokine-mediated inflammatory response that occurs in IBD induces lethargy and hypersomnia.…”
Section: Sleep Deprivation and Ibdmentioning
confidence: 99%
“…placebo response) all are related to the concept that stress reduction will improve not only the patients' sense of well being, but potentially their chronic inflammatory disease. New data by Szigethy and colleagues have suggested that the use of cognitive behavioral therapy, which is a well established approach for stress reduction, and relaxation therapy may actually help resolve depression in adolescents with IBD [49,52,53] . These investigators were also able to demonstrate in preliminary data that children receiving cognitive behavioral therapy were also shown to decrease C reactive protein elevation in a pilot study.…”
Section: Cognitive Behavioral Therapy/stress Coping In Ibdmentioning
confidence: 99%
See 1 more Smart Citation